The effect of covid-19 anxiety on sexual function of health care providers; a cross-sectional survey study - Firouzabadi, Maryam; a, a; Alavi-Arjas , Fatemeh; Balvardi, Mohadeseh; Badrabadi , Neda (Medicinski časopis, 2022)
Introduction: Coronavirus disease epidemic in 2019 (COVID-19) posed a big challenge to healthcare providers. Objectives: The present study aimed to explore the relationship between coronavirus anxiety and the sexual function of healthcare providers. Methods: In this study, an online non-probability sample survey was used to explore the relationship between anxiety and sexual function in health care providers during COVID-19 pandemic. The questionnaire included Female Sexual Function Index (FSFI) and Corona Disease Anxiety Scale (CDAS). Result: A total of 300 health care providers were investigated in this study. The estimated self-reported rates of mild anxiety symptoms were 49%, moderate 29.2% and severe were 29.9%. the total mean score of FSFI of healthcare providers were (19.1 (SD=4.4)). The results showed that on the total scale, 40.9% of health care providers had mild anxiety. The results also indicated that female sexual function is inversely correlated with Corona anxiety. Also, it was shown that corona anxiety is inversely correlated with sexual functioning. Conclusions: this study concluded the negative impact of the COVID-19 pandemic on anxiety and sexual function in healthcare providers. Therefore, psychological or sexual assistance may be beneficial. Keywords: sexual function; anxiety; healthcare provider; Coronavirus pandemic